A Distributed Power Allocation Scheme for Base Stations Powered by Retailers with Heterogeneous Renewable Energy Sources. Issue 4 (1st August 2016) - Jeon, Seung Hyun; Lee, Joohyung; Choi, Jun Kyun
Abstract : Owing to the intermittent power generation of renewable energy sources (RESs), future wireless cellular networks are required to reliably aggregate power from retailers. In this paper, we propose a distributed power allocation (DPA) scheme for base stations (BSs) powered by retailers with heterogeneous RESs in order to deal with the unreliable power supply (UPS) problem. The goal of the proposed DPA scheme is to maximize our well‐defined utility, which consists of power satisfaction and unit power costs including added costs as a non‐subscriber, based on linear and quadratic cost models. To determine the optimal amount of DPA, we apply dual decomposition, which separates the master problem into sub‐problems. Optimal power allocation from each retailer can be obtained by iteratively coordinating between the BSs and retailers. Finally, through a mathematical analysis, we show that the proposed DPA can overcome the UPS for BSs powered from heterogeneous RESs.